Protease-degradable hydrogels with multifunctional biomimetic peptides for bone tissue engineering - Oliver-Cervelló, Lluís; Martin-Gómez, Helena; Gonzalez-Garcia, Cristina; Salmeron-Sanchez, Manuel; Ginebra, Maria-Pau; Mas-Moruno, Carlos (Frontiers in Bioengineering and Biotechnology, 2023)
Mimicking bone extracellular matrix (ECM) is paramount to develop novel biomaterials for bone tissue engineering. In this regard, the combination of integrin-binding ligands together with osteogenic peptides represents a powerful approach to recapitulate the healing microenvironment of bone. In the present work, we designed polyethylene glycol (PEG)-based hydrogels functionalized with cell instructive multifunctional biomimetic peptides (either with cyclic RGD-DWIVA or cyclic RGD-cyclic DWIVA) and cross-linked with matrix metalloproteinases (MMPs)-degradable sequences to enable dynamic enzymatic biodegradation and cell spreading and differentiation. The analysis of the intrinsic properties of the hydrogel revealed relevant mechanical properties, porosity, swelling and degradability to engineer hydrogels for bone tissue engineering. Moreover, the engineered hydrogels were able to promote human mesenchymal stem cells (MSCs) spreading and significantly improve their osteogenic differentiation. Thus, these novel hydrogels could be a promising candidate for applications in bone tissue engineering, such as acellular systems to be implanted and regenerate bone or in stem cells therapy.